Patriarchy and khul': women's struggle for equal rights in pre and post revolution Egypt - Elafify, Nada (AUC Knowledge Fountain, 2013)
Societal perceptions and the patriarchal structure dictated by our culture has manifested itself though the implementation and interpretations of the laws, which undermine the theoretical benefits of khul’. Prior to 2000, women were only allowed to obtain a divorce based on limited grounds and the judge’s consent. The ongoing resistance to the khul’ law of 2000 highlights the inadequate ability of legal reform to have a transformative effect on women’s position in society. This thesis examines the challenges that the khul’ law no.1/2000 continues to confront from early opposition to the renewed scrutiny in post Mubarak Egypt. The legal and social hurdles put forth by the state as well as rise of Islamists and women’s right’s slow advancement in society are examined, highlighting that the resistance is based on patriarchal beliefs and societal perceptions of women. This paper further examines the role of legal reform in providing revolutionary change in Egypt and whether adopting law has, in fact, advanced women’s position in society. Over a decade after its enactment, khul’ is still resisted and even threatened in post revolutionary Egypt. I argue that the patriarchal beliefs embedded in our society and manifested through state imposed barriers and interpretations of the law directly undermine the purpose of legal reform and the ability of the law to achieve the desired change.